Protection of Human Rights of Migrant Women - Mršević, Zorica; Janković, Svetlana (Zbornik Instituta za kriminološka i sociološka istraživanja, 2019)
Authors analyze migration as a gender-differently profiled phenomenon, given that the position of migrant women differs substantially from the position of migrant men throughout the entire migration cycle. There are presented the documented gender-differentiated forms of human rights violations migrant women suffer in countries of origin, transit and destination countries, specificities regarding legal migration status, sectors in which they migrate, forms of gender-based abuse that occur at almost all stages of the migration cycle. Exposed and anlysed are the factors affecting the migration of women, circumstances that contribute to the particular vulnerability of many migrant women and their dealing with gender- based discrimination as causes and consequences of violations of their human rights. Finally, special attention is paid to human rights and gender equality standards, as well as to international recommendations for the protection of the human rights of migrant women, which promote safe migration procedures and the obligation of all states to respect, protect and implement the human rights of women during the migration cycle.